2016
DOI: 10.1016/j.jct.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid equilibria for ternary systems polyoxymethylene dimethyl ethers + para-xylene + water

Abstract: Polyoxymethylene dimethyl ethers (PODEn) are promising diesel additives which can be synthesized from formaldehyde and methanol. In this work, the ternary liquid-liquid equilibria (LLE) were analytically determined at 293.15 K and 313.15 K for the following systems: PODE1+para-xylene(PX)+water, PODE2+PX+water, PODE3+PX+water, PODE4+PX+water, respectively. The isothermal experimental results have shown a good linear fit in Hand plots and the Othmer-Tobias. The design of the solvent extraction equipment for extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…The mutual solubility of ternary liquid–liquid equilibria for water + PODE 1–4 + o -xylene was measured by analyzing the composition of equilibrated two liquid phases in a thermostated flask. The LLE determination apparatus of this work was similar to that in our previous work . The temperature of the experiment was controlled steadily and accurately by a constant temperature circulating water device.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutual solubility of ternary liquid–liquid equilibria for water + PODE 1–4 + o -xylene was measured by analyzing the composition of equilibrated two liquid phases in a thermostated flask. The LLE determination apparatus of this work was similar to that in our previous work . The temperature of the experiment was controlled steadily and accurately by a constant temperature circulating water device.…”
Section: Methodsmentioning
confidence: 99%
“…Kuhnert et al researched ternary systems (formaldehyde + water + methylal) and (formaldehyde + methanol + methylal) and a quaternary system (formaldehyde + water + methanol + methylal) and found that the experimental results were consistent with the predicted results. Zhuang et al measured the LLE data for ternary systems (PODE 1–4 + p -xylene + water) and found that the UNIQUAC model showed a better correlation for ternary systems than the NRTL model. There are few available literature studies about LLE data on these ternary systems.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O management remains a key hurdle for the realization of a scalable OME 3-5 production. Research and development focused in the last decades on various H 2 O separation strategies, such as extraction [78][79][80][81][82][83][84][85], adsorption [76,86], or membranes [87]. The long-term stability of the materials applied for the previous concepts, as well as the efficiency and the scalability of these approaches are crucial for their application and remain under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…34 Thus, the effects of hydrophobic property of acid catalyst on the process of methanol and formaldehyde aqueous solution to PODE have been investigated in this paper. The experimental results exhibited that the hydrophilic catalysts present excellent performance for the reaction of methanol and formaldehyde to methylal because of the hydrophilic property of methanol and formaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hydrophilic catalysts show limited performance for the process of methylal to PODE 2 and the process of PODE n to PODE n + 1 because of the hydrophobic properties of methylal and PODE. 34 Thus, the effects of hydrophobic property of acid catalyst on the process of methanol and formaldehyde aqueous solution to PODE have been investigated in this paper.…”
Section: Introductionmentioning
confidence: 99%